Colour image watermarking using discrete cosine transform and two-level singular value decomposition - Ali, Bokan Omar (2013)
Digital image watermarking is a technique used for hiding digital information in a carrier image. It is predominantly used for copyright protection against copyright infringement and malicious attacks. Embedding a watermark in the frequency domain is becoming more attractive for the majority of researchers as it can provide better performance. In this research, colour image watermarking using Discrete Cosine Transform (DCT) and two-level Singular Value Decomposition (SVD) is proposed. First step is preparing RGB colour image as the cover image and greyscale image as the watermark. The RGB host image is divided into R, G and B channels and the B channel is then selected. The selected channel is then divided into non-overlapping square blocks of (4x4) pixels to match the watermark size. Next, the DCT is applied to each block. DC component is then retrieved and collected from each block in order to obtain a new block of (128x128) pixels. Following that, SVD is applied to the block to generate three matrices, U, S and V. Finally, the greyscale watermark is embedded in the S matrix. Once the embedding is completed, the R, G and embedded B channel are then merged to obtain a watermarked image. Experimental results show that the average PSNR value is higher than 53 dB, which means that the proposed method is imperceptible to naked eyes. Also, the average NCC value is higher than 0.97, which indicates the proposed method has strong robustness against major attacks.